Theories of international business (Sydney : Australian Centre for International Business)
An inevitable challenge facing both scholars and practitioners of international business is the interaction between MNE strategy and government policy at the multinational, national nd sub-national levels. Drawing on his research with Professor Alain Verbeke, published in Journal of International Business 1998, Professor Rugman explores a wide span of literature over the past 40-50 years that addresses this issue from the perspective of managers of MNEs, as well as those of home and host governments. Professor Rugman critiques the shifts in the focus of the literature over this period, and raises a number of current challenges to our thinking about Theories of International Business.
Editor: Sara L. McGaughey, William R. Purcell
Presenter: Professor Alan Rugman
Keywords: International trade; International finance; Investments, Foreign